Diagnosis and Management of Acute Respiratory Tract Infections (Pharyngitis and Laryngitis) - Salsabila, Ericha Zabrina; Damayanti, Ida Ayu Andara; Wiguna, I Made Danuarta; Maulana, Muhammad Rafi; Ajmala, Indana Eva (Jurnal Biologi Tropis, 2025)
Acute respiratory tract infections (ARI), including pharyngitis and laryngitis, remain a highly prevalent disease in Indonesia and even globally. These respiratory infections are caused by the bacterium Streptococcus pyogenes, also known as Streptococcus beta hemolyticus group A. The purpose of this literature review was to identify acute respiratory tract infections (pharyngitis and laryngitis). Pharyngitis is more common in children and adolescents, while laryngitis is more common in infants and children. The review concluded that Streptococcus pyogenes is the main cause of bacterial pharyngitis, while laryngitis is an inflammation of the larynx that can be caused by a variety of factors, including bacterial or viral infections as well as non-infectious factors like irritation or trauma. In conclusion, a thorough understanding of acute pharyngitis and laryngitis, including causative factors, clinical manifestations, management, and prevention, is essential for both medical personnel and the general public in an effort to reduce the burden of these diseases and improve overall upper respiratory health.